Hydrodynamic characteristics of Khor Al-Zubair Channel, Southern Iraq - Ali,; S. abdullah, Sadiq (Vietnam Journal of Marine Science and Technology, 2025)
The hydrodynamic features of the Khor Al-Zubair, a mixed, predominantly semidiurnal tidal channel situated in Southern Iraq at the northwest tip of the Arabian Gulf, were investigated using in situ measurements taken in 2015. The data utilized in this study, which spanned nearly a year, is unique, particularly for currents and waves, which were never previously available in this area. The results illustrated that the water level exhibited a spatial and temporal variation ranging from hourly to seasonal oscillation. However, the hourly water level highest annual range recording during the study period at St1 (Umm Qasar port) and St2 (Khor Al-Zubair port) was about 4.77 and 5.88 m, respectively. Correspondingly, the results showed that the current speed is high at both flood and ebb tides, exceeding 1 m/sec, and in general, the ebb currents are stronger than the flood currents. The highest current measured was 1.83 m/sec. Moreover, the results revealed that the highest and lowest wave height (Hs) recordings in the Khor Al-Zubair channel (KAZC) reached 0.22 and 0.03 m, respectively. Correspondingly, our results demonstrated that the wave period’s maximum, minimum, and average were 5.51, 3.96, and 4.5 sec, respectively.